Medical terminology. Latin is the only source of international terminology (Texas Journal of Multidisciplinary Studies, 2026)
This article discusses the fundamental role of the Latin language in medicine, its importance in global scientific communication and clinical The laws of terminology formation are highlighted. The morphological structure, semantic accuracy and deontological significance of medical terms are also analyzed in depth. The Latin language is not only a system of terms, but also a universal linguistic basis of medical science.